La organización comunitaria frente a la inseguridad ciudadana en la parroquia Caña Quemada del cantón Pasaje, provincia de El Oro. Año 2013 - Arias Zari, Zibila Vivyek (2015)
This project ". The Community Organization versus Citizen Insecurity in the parish Caña Quemada, Canton Pasaje, El Oro Province Year 2013" will contribute to improving the quality of life of the inhabitants, to build a strong organization Community enabling them to live in harmony, with the inhabitants the main executors of this project, they have a clear view that that through the restoration of values and community work should become an integral process that society plays in the sociocultural environment and above all human. Due to insecurity affects all population sectors of Ecuador and in recognition of the rights of the good life that every citizen has the state is responsible for compliance.